Plasma free reversible and irreversible microfluidic bonding. Issue 2 (19th December 2016) - Chu, M.; Nguyen, T. T.; Lee, E. K.; Morival, J. L.; Khine, M.
Abstract : We demonstrate a novel bonding process that allows for facile multilayer microfluidic chip fabrication and is compatible with cell micropatterning. Abstract : We demonstrate a facile, plasma free process to fabricate both reversibly and irreversibly sealed microfluidic chips using a PDMS-based adhesive polymer mixture. This is a versatile method that is compatible with current PDMS microfluidics processes. It allows for easier fabrication of multilayer microfluidic devices and is compatible with micropatterning of proteins for cell culturing. When combined with our Shrinky-Dink microfluidic prototyping, complete microfluidic device fabrication can be performed without the need for any capital equipment, making microfluidics accessible to the classroom.